Penggunaan Smartphone dengan Frekuensi Akses Pronografi dan Dampaknya terhadap Perilaku Seks Bebas pada Remaja - Wahyu Agung Budi Alamsyah; Fatma Tiara Sari; Ana Rizqy Soliha; Nur Mufida Wulan Sari; Irwanto Irwanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine whether there is a relationship between smartphone use and the frequency of access to pornography and free sex behavior among adolescents at SMK Negeri 2 Samarinda. Methods This study uses quantitative research with a cross-sectional design. The results showed that students of class XI SMK Negeri 2 Kota Samarinda had Moderate Smartphone Usage Behavior totaling 205 respondents (93.2%). They then obtained pornographic access behavior as Moderate at 174 (79.1%). And low free-sex behavior is 168 (76.4%). The result is a significance value of 0.651 (p-value > 0.05), so there is no significant relationship between smartphone use and free sex behavior in SMK Negeri 2 Kota Samarinda students. These results obtained a significance value of 0.125 (p-value> 0.05), indicating a significant relationship between the frequency of access to pornography and free sex. In conclusion, adolescents' insights about the dangers and impacts of having free sex should be wiser in using smartphones and minimizing access to pornography to avoid free sex. Keywords: Frequency of Access to Pornography, Smartphone Use, Free Sexual Behavior